2013
DOI: 10.1089/ten.tea.2013.0256
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osteogenesis in Cocultures with Human Mesenchymal Stem Cells and Endothelial Cells on Polymeric Microfiber Scaffolds

Abstract: In this work, human mesenchymal stem cells (hMSCs) and their osteogenically precultured derivatives were directly cocultured with human umbilical vein endothelial cells (HUVECs) on electrospun three-dimensional poly(e-caprolactone) microfiber scaffolds to evaluate the coculture's effect on the generation of osteogenic constructs. Specifically, cells were cultured on scaffolds for up to 3 weeks, and the cellularity, alkaline phosphatase (ALP) activity, and bone-like matrix formation were assessed. Constructs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 44 publications
(105 reference statements)
3
40
0
Order By: Relevance
“…3, 12, 21, 32 Furthermore, previous studies from our laboratories have demonstrated that co-culturing osteogenically precultured hMSCs with HUVECs in a 1:1 ratio under static conditions led to enhanced osteogenic differentiation compared to cultures of hMSCs alone. 9 Both cell populations have previously been shown to be highly responsive to mechanical forces, 1, 16, 22 and the effect of mechanical stimulation on the behavior of endothelial cells and vascularization in co-cultures has been investigated. 18, 24 However, the effect of mechanical forces on the osteogenic differentiation of hMSC/HUVEC co-cultures has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 12, 21, 32 Furthermore, previous studies from our laboratories have demonstrated that co-culturing osteogenically precultured hMSCs with HUVECs in a 1:1 ratio under static conditions led to enhanced osteogenic differentiation compared to cultures of hMSCs alone. 9 Both cell populations have previously been shown to be highly responsive to mechanical forces, 1, 16, 22 and the effect of mechanical stimulation on the behavior of endothelial cells and vascularization in co-cultures has been investigated. 18, 24 However, the effect of mechanical forces on the osteogenic differentiation of hMSC/HUVEC co-cultures has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…9 In order to better recapitulate the bone marrow perivascular niche, the dynamic mechanical environment in vivo should also be considered in an in vitro co-culture system. 13 Flow perfusion bioreactor systems can be used to apply mechanical stresses to three-dimensional cell cultures.…”
Section: Introductionmentioning
confidence: 99%
“…166ā€“168 It has been suggested that MSCs are the major producer of VEGF during vascular bone regeneration. 101,167,169 These MSC secreted pro-angiogenic factors stimulate EPC proliferation and differentiation, which in turn causes EPCs to secrete osteogenic growth factors that stimulate MSC differentiation.…”
Section: Role Of Stem Cells In Vascularized Bone Regenerationmentioning
confidence: 99%
“…Unexpectedly, even before a mature vascular network is formed, ECs can affect co-cultured cells and influence the surrounding microenvironment. When mixed with MSCs, for example, ECs enhance osteogenic matrix production within 3D PCL scaffolds [210, 211]. …”
Section: Future Directionsmentioning
confidence: 99%
“…A step in this direction, human MSCs, which could serve as a precursor for ES, and human umbilical vein endothelial cells (HUVECs) were co-cultured in 3D PCL-scaffolds under conditions of flow perfusion. Superior proliferation of both cell lines was achieved and the spatial distribution was more uniform throughout 3D-PCL scaffolds [213]. Since VEGF secretion by human ES tumors has been shown to encourage CD38- primitive MSCs to migrate from the bone marrow to the tumor, where they differentiate into ECs and/or pericytes capable of angiogenesis and vasculogenesis [198-201], it would be intriguing to know whether a similar effect could be replicated within a tissue-engineered ES model.…”
Section: Future Directionsmentioning
confidence: 99%